Contrast-enhanced ultrasonography for the management of portal hypertension in cirrhosis - Maruyama, Hitoshi; Tobari, Maki; Nagamatsu, Hiroaki; Shiina, Suichiro; Yamaguchi, Tadashi (Frontiers in Medicine, 2022)
Portal hypertension is the major pathophysiology of patients with cirrhosis. It accounts for the occurrence and the severity of various manifestations. The degree is determined by the portal pressure or hepatic venous pressure gradients, both are obtained by invasive procedures of interventional radiology. Ultrasound (US) represents a simple and less-invasive imaging modality for the diagnosis of liver diseases. Because of the availability of microbubble-based contrast agents and development of imaging mode corresponding to contrast effect, contrast-enhanced US (CEUS) has become spread worldwide and popular for the detailed evaluation of hepatic hemodynamics, diffuse liver disease and focal hepatic lesions. A recent advancement of digital technology has gained the ability of contrast-based demonstration with improved resolution, leading to a wider range of applications. This review article describes the current role, benefits, and limitations of CEUS for the management of portal hypertension.